Improvement of Small Ruminant Production Systems in Rainfed Agro-Ecological Zones of Asia - Devendra, C (Annals of Arid Zone, 2016)
Small ruminants (goats and sheep) form an important economic and ecological niche in Asian mixed farming systems. This is reflected in their wide distribution across ecosystems, value as genetic resources, productivity and significance of ownership. Approximately 60% of the 674 million goats and 20% of the 1048 million sheep are found in Asia. India, China, Pakistan and Bangladesh account for about 84%, and China, India and Pakistan, 72% of the total populations of goats and sheep, respectively in Asia. They are concentrated mainly in rainfed semi-arid and arid, and sub-humid and humid lowland and upland areas in mixed farm situations, where about 83% of the total small ruminant populations can be found. Their ownership, especially by poor people, is associated with several objectives to meet short-term socio-economic needs, security and survival in which these species enable diversification of resources to reduce risks, alleviation of poverty, promotion of linkages between system components, and stability of farm households. Prevailing small ruminant production systems are described. The opportunities for research are considerable and are indicated. The strategy for increasing their contribution involves more attention to the rainfed lowland and upland areas, more efficient use of the available breeds, targeting the poor to address poverty, and wider use of improved technologies through community-based participation that address both improved production and post-production systems.